2020
DOI: 10.1055/s-0040-1715164
|View full text |Cite
|
Sign up to set email alerts
|

Driving Factors of Preterm Birth Risk in Adolescents

Abstract: Objective We examined rates of spontaneous and indicated preterm births (S-PTB and I-PTB, respectively) and clinical risk factors for PTB in adolescents. Study Design This is a population-based, retrospective cohort using 2012 U.S. natality data of nulliparous women who delivered a nonanomalous singleton birth between 20 and 42 weeks' gestation. Maternal age included <16, 16 to 19.9, and ≥20 years. Rates of total, S-PTB, and I-PTB were compared across age groups. Multinomial logistic regression te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The finding is similar to findings from several other studies across the globe [35,36]. Although the biological link between teenage pregnancy and PB is not properly understood, [10,37] pregnant teens are likely to be disfavoured in several aspects such as education, access to care and nutrition compared to older mothers [38][39][40].…”
Section: Discussionsupporting
confidence: 87%
“…The finding is similar to findings from several other studies across the globe [35,36]. Although the biological link between teenage pregnancy and PB is not properly understood, [10,37] pregnant teens are likely to be disfavoured in several aspects such as education, access to care and nutrition compared to older mothers [38][39][40].…”
Section: Discussionsupporting
confidence: 87%
“…The recently reported incidence of preterm in Thailand was about 10-13% [41]. In our study, we had sPTD incidence of 8.5%, while other studies reported incidences between 7.8-10.6 % [42,43]. There are numerous risk factors involved with preterm delivery such as a previous history of preterm birth, some medical diseases or hypertension associated with pregnancy [40,42,44,45].…”
Section: Discussionmentioning
confidence: 51%
“…In our study, we had sPTD incidence of 8.5%, while other studies reported incidences between 7.8-10.6 % [42,43]. There are numerous risk factors involved with preterm delivery such as a previous history of preterm birth, some medical diseases or hypertension associated with pregnancy [40,42,44,45]. However, a considerable number of preterm deliveries have no clear risk factors, especially in the sPTD group [43,46,47].…”
Section: Discussionmentioning
confidence: 57%
“…Newborn babies are very special. They do not have any previous medical background, and their early neonatal path is directly connected to the maternal history of their mothers [ 5 7 ]. The healthcare services also incorporate the arrangements of essential social and economic support for women before, during, and after pregnancy including educational, medical, and other training programs that facilitate healthy motherhood.…”
Section: Introductionmentioning
confidence: 99%